Indigenous Knowledge and Literacy Acquisition: A Qualitative Study of Low-Literate Elder Refugees’ Educational Backgrounds and Cultural Dissonance - Vogl, Lisa (LESLLA Symposium Proceedings, 2019)
Prior knowledge is central to memory and learning, but many older refugees come to the classroom with ways of knowing and experiences much different from what they find in Western teaching contexts. In describing refugees’ prior learning experiences, research often cites ethnological differences between print-based cultures and oral traditions. But relatively few researchers cite adult learners’ own words when describing these differences. In this study, elder refugees’ narratives illuminate our understanding of indigenous knowledge, which is passed down orally through generations, and is specific to the place where they lived. What happens to this place-based knowledge when they must leave their country? By analyzing themes from a qualitative study with low-literate elder refugees from Somalia, their instructor, and observations within a beginning language and literacy class in the U.S., this research seeks to broaden critical discourse around LESLLA learners in general and elder learners aged 60 and older in particular.